Seismic Behaviour of Multistorey Steel Framed Tall Buildings Using Intentionally Eccentric Braces - Nima Gholizadeh; Feng Fu (Shock and Vibration, 2023)
Braces with intentional eccentricity (BIE) are recently proposed to improve the seismic behaviour of conventional buckling braces (CBBs) by inserting intentional eccentricity along the brace length. Due to this eccentricity and the resultant bending moment, the BIE bends uniformly from small storey drifts and moves smoothly into the postbuckling behaviour under compression and sustains trilinear behaviour under tension. This behaviour delays the appearance of midlength local buckling which causes unstable energy dissipation. BIEs have a desirable postyielding stiffness which results in stable energy dissipation during cyclic loading and are capable of dissipating energy during low-intensity earthquakes. The seismic behaviour of structures with BIEs for use in buildings has not yet been investigated, specifically in tall buildings. Therefore, this study concentrates on investigating the seismic behaviour of tall buildings equipped with BIEs that uses a 3-dimensional (3D) finite element model in ETABS. In the first step, a 20-storey structure is designed using both eccentric brace frame (EBF) and BIE system and their seismic performance under the TABAS earthquake record is compared. In the second step, the seismic performance of a 25-storey irregular structure is assessed to evaluate the efficiency of the BIE system in irregular structures. Results show the desirable performance and energy dissipation capacity of the BIE system but it also shows large out-of-plane deformation in some cases.